Evaluation of selected fungicide treatment for the control of seedborne fungal pathogens in forage germplasm - Dawit, Woubit; Mulatu, Fikerte; Hirko, Mignote; Negawo, Alemayehu T. (International Livestock Research Institute, 2025)
Seedborne fungal pathogens pose a significant threat to seed quality, germination, and crop establishment, and can spread through international germplasm exchange, creating serious biosecurity risks. This study evaluated the efficacy of selected fungicides as seed treatment for controlling seedborne fungi in forage germplasm. The seeds of five forage accessions with a history of fungal infections were treated with SAAF (Carbendazim 12% + Mancozeb 63% WP), Apron Star (Thiamethoxam 20% + Metalaxyl-M 20% + Difenoconazole 2% WS), Carbendazim (Carbendazim 50% WP), and untreated control. The fungicide-treated seeds were incubated on moist blotter paper and Potato Dextrose Agar (PDA) at 23 ± 1 °C for seven days and then examined for fungal infection. Treatment efficacy was assessed based on the incidence of infected seeds, diversity of fungal genera, and percentage reduction relative to untreated controls. Results showed that SAAF exhibited the highest efficacy, achieving a 96.60% reduction in seed infection, followed by Carbendazim (50%) and Apron Star (48%). The untreated seeds (control) recorded a 44.29% infection incidence, with multiple pathogens detected including Alternaria, Fusarium, Aspergillus, and Phoma. Overall, the results demonstrate the superior performance of SAAF, formulated with carbendazim and mancozeb, providing the most effective suppression of a broad range of seedborne fungi. Fungicide seed treatment, especially with SAAF, therefore, offers an effective strategy for improving seed health and reducing the risk of pathogen dissemination with seeds